Strategi Pemilihan Media Partner dan Influencer Dalam Penyelenggaraan Pameran CRAFINA 2019 - Sakana Bill Haqi; Imam Syafganti (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2020)
This research discusses the strategy of selecting media partner and influencer in promotional activities at theCRAFINA 2019 exhibition. The purpose of this research is to understand the process in the selection strategy of mediapartner and influencer in promotional activities in organizing exhibition from the planning stage of the strategy to theimplementation. This research used qualitative research methods. Data collection techniques using interviews,observation and documentation. The focus of the research was conducted at the 2019 CRAFINA exhibition at theJakarta Convention Center. The results of this research identified that There are three factors in the selection ofmedia partners and influencers, namely the budget for the promotion of the exhibition, the conformity with the conceptof the exhibition and the system of media partner cooperation and there were two stages in the strategy of selectingmedia partner and influencer in organizing the exhibition, namely planning and implementation. At the planning stagethe activities carried out are the making of promotional plans that contain media partner and influencer targets, createa media and influencer database that matches the targets of the promotion plan and make proposals for submittingcooperation to be sent to the target media partner and influencer.